Co-existence of social isolation and homebound status increase the risk of all-cause mortality. (19th July 2018) - Sakurai, Ryota; Yasunaga, Masashi; Nishi, Mariko; Fukaya, Taro; Hasebe, Masami; Murayama, Yoh; Koike, Takashi; Matsunaga, Hiroko; Nonaka, Kumiko; Suzuki, Hiroyuki; Saito, Masashige; Kobayashi, Erika; et al.
ABSTRACT: Background: Social isolation and homebound statuses are possible risk factors for increased mortality among older adults. However, no study has addressed the impact of accumulation of these two factors on mortality. The aim of this study was to examine whether such accumulation increased the risk of all-cause mortality. Methods: The analyzed sample was drawn from a mail survey of 1, 023 older adults without instrumental activities of daily living disability. Participants were classified into four groups according to the frequency of both face-to-face and non-face-to-face interactions with others (social isolation and non-social isolation) and the frequency of going outdoors (homebound and non-homebound). Social isolation and homebound statuses were defined as having a social interaction less than once a week and going outdoors either every few days or less, respectively. All-cause mortality information during a six-year follow-up was obtained. Results: In total, 78 (7.6%) participants were both socially isolated and homebound. During the follow-up period, 65 participants died, with an overall mortality rate of 10.6 per 1000 person-years. Cox proportional hazards regression analyses demonstrated that older adults who were socially isolated and homebound showed a significantly higher risk of subsequent all-cause mortality compared with healthy adults who were neither socially isolated nor homebound, independent of potential covariates (aHR, 2.19; 95% CI: 1.04–4.63). Conclusion: Our results suggest that the co-existence of social isolation and homebound statuses may synergistically increase risk of mortality. Both active and socially integrated lifestyle in later life might play a major role in maintaining a healthy status.